Expression of trophoblast derived prostaglandin E2 receptor 2 (EP2) is reduced in patients with recurrent miscarriage and EP2 regulates cell proliferation and expression of inflammatory cytokines. (November 2020) - Peng, Lin; Ye, Yao; Mullikin, Heather; Lin, LiLi; Kuhn, Christina; Rahmeh, Martina; Mahner, Sven; Jeschke, Udo; von Schönfeldt, Viktoria
Highlights: EP2 was significantly decreased in trophoblasts and decidua of the uRM group compared with the normal group. The reduced levels of EP2 observed in uRM may contribute to reduced trophoblast proliferation. In addition, selective EP2 antagonists inhibited trophoblast production of beta-hcG, IL-6 and IL-8 and elevated secretion of PAI-1 and TNF-α. The aberrant release of cytokines (IL-6, IL-8, and TNF-α) by trophoblasts can potentially affect trophoblast cell function. Abstract: Backgroud: Prostaglandin E2 (PGE2), an inflammatory mediator, modulates cytokines, regulates immune responses in reproductive processes and stimulates inflammatory reactions via the prostaglandin E2 receptor 2 (EP2). However, the regulatory effects of EP2 signaling on trophoblasts and its role in unexplained recurrent miscarriage (uRM) remains unclear. Patients and methods: A total of 19 placentas from patients with a history of more than two consecutive pregnancy losses of unknown cause (uRM group) and placentas of 19 healthy patients following a legal termination of their pregnancy were used for PGE2 receptor (EP1, EP2 and EP4) expression analyses via immunohistochemistry. Double immunofluorescence was also used to identify EP2 expressing cells in the decidua. Finally, HTR-8/SVneo cells were used to clarify the role of EP2 in in vitro experiments. Results: The expression of EP2 and EP4 was found to be reduced in the syncytiotrophoblast and decidua of uRM patients. A selective EP2 receptor antagonist (PF-04, 418, 948) reduced the proliferation and secretion of ß-hCG, inhibited interleukin -6 (IL-6) and interleukin-8 (IL-8) and up-regulated the production of the tumor necrosis factor-α (TNF-α) and plasminogen activator inhibitor type 1 (PAI-1) in HTR-8/SVneo cells in vitro . Conclusion: PGE2-EP2 signaling pathway may represent a novel therapy option for uRM. The involvement of EP2 in uRM acts perhaps via inflammatory cytokines and indicates that the PGE2-EP2 signaling pathway might represent an unexplored etiology for uRM.